Efficacy of exercise training in pulmonary arterial hypertension associated with congenital heart disease - Becker-Grünig, Tabea; Benjamin, Nicola; Lichtblau, Mona; Nagel, Christian; Fischer, Christine; Gorenflo, Matthias; Grünig, Ekkehard (International journal of cardiology, 2013)
Background: The objective of this prospective study was to assess the efficacy of exercise training as add-on to medical therapy in patients with congenital heart disease associated pulmonary arterial hypertension (CHD-APAH). Methods: Patients with invasively confirmed CHD-APAH received in-hospital exercise training for 3weeks and continued at home. Efficacy parameters were evaluated at baseline, after 3 and 15weeks. Medical treatment remained unchanged. Worsening events and survival rate were assessed in a follow-up period of 21±14months. Results: Twenty consecutive CHD-APAH patients (16 female, 4 male, mean pulmonary arterial pressure 60±23mmHg) were included. Patients significantly improved the mean distance walked in 6min compared to baseline by 63±47m after 3weeks (p<0.001) and by 67±59m after 15weeks (p=0.001). Quality of life-score (p=0.05), peak oxygen consumption (p=0.002) and maximal workload (p=0.003) improved significantly by exercise training after 15weeks. The 1- and 2‐year survival rates were 100%, the transplantation-free survival rate was 100% after 1year and 93% after 2years. Conclusion: Exercise training as add-on to medical therapy may be effective in patients with CHD-APAH and improved work capacity, quality of life and further prognostic relevant parameters. It was associated with an excellent long-term survival. Further randomized controlled studies are needed to confirm these results.